Characterization of Metabolites and Transcripts Involved in Flower Pigmentation in Primula vulgaris - Li, Long; Ye, Jing; Li, Houhua; Shi, Qianqian (Frontiers in Plant Science, 2020)
Primula vulgaris exhibits a wide range of flower colors and is a valuable ornamental plant. The combination of flavonols /anthocyanins and carotenoids provides various colorations ranging from yellow to violet-blue. However, the complex metabolic networks and molecular mechanisms underlying the different flower colors of P. vulgaris remain unclear. Based on comprehensive analysis of morphological anatomy, metabolites and gene expression in different-colored flowers of P. vulgaris, the mechanisms relating color-determining compounds to gene expression profiles were revealed. In the case of P. vulgaris flower color, hirsutin, rosinin, petunidin- and cyanidin-type anthocyanins and the copigment herbacetin contributed to the blue coloration, whereas peonidin-, cyandin- and delphinidin-type anthocyanins showed high accumulation levels in pink flowers. The color formation of blue and pink were mainly via the regulation of F3′5′H (c53168), AOMT (c47583, c44905) and 3GT (c50034). Yellow coloration was mainly due to gossypetin and carotenoid, which regulated by F3H (c43100), F3′H (c53714), 3GT (c53907) as well as many carotenoid biosynthetic pathway-related genes. Co-expression network and transient expression analysis suggested a potential direct link between flavonoid and carotenoid biosynthetic pathways through MYB transcription factor regulation. This work reveals that transcription changes influence physiological characteristics and biochemistry characteristics and subsequently results in flower coloration in P. vulgaris.